Hubungan Antara Kemandirian Belajar dan Indeks Prestasi Mahasiswa Program Studi Pendidikan Kimia dalam Penggunaan Google Classroom - Muhajjir, Ahmad Ridho; Hairida, Hairida; Rasmawan, Rahmat; Erlina, Erlina; Sartika, Rody Putra (Universitas Tanjungpura, 2023)
The purpose of this study was to determine the relationship between independence learning and GPA in the use of Google Classroom. This research uses a correlation study approach. The data collection tool used is a questionnaire using a Likert scale. The population in this study were Chemical Education Students, FKIP Untan, Batch 2021. The samples taken were 43 respondents. The results of data analysis using the analysis prerequisite test with a significance level of 0.05 indicate that the learning independence data variable is normally distributed and the GPA is not normally distributed which is transformed with a significance of 0.288 so that the research variable data has a normal distribution. The results of the linearity test show that the regression line is linear. The results of the analysis of hypothesis testing using the Product Moment Correlation show that there is no positive and significant relationship between Independence Learning and the Cumulative Achievement Index. Product Moment correlation analysis rcount of -0.025. This value is smaller than rtable with N=43 at the 5% significance level of 0.2940. This means that Learning Independence has no positive impact and does not significantly affect student GPA on the use of Google Classroom.